Meningkatkan Kepuasan Kerja Melalui Penerapan Pembelajaran Dalam Media Sosial Bagi Guru Pendidikan Agama Kristen - Chris Pasuhuk; Bernadetha Nadeak; Djoys Anneke Rantung; Lamhot Naibaho (Jurnal Ilmiah Wahana Pendidikan, 2023)
Job satisfaction encourages employees to increase performance, commitment to the organization, reduce absenteeism and increase interest in the profession. It is equally important in the private and public sectors, in developed and developing countries and is an important issue to be considered in educational institutions. Learning in social media is a relatively new theory compared to other learning theories. Learn through interaction with a community of experts and fellow learners. Communication between participants relies on social networking media such as online discussions, blogging, vlogging and text messaging. As we know, there are a lot of social media that are currently used by people, especially Indonesia, namely Facebook, Twitter, Google+, LinkedIn, Instagram, Pinterest, Tiktok, Youtube and others. To apply learning in social media we must pay attention to the features that can be used from each of these social media so that they can support a learning process. Then, determine which social media is suitable for the learning process you want to build. Learning in social media, there are many ways to interact between teachers and students with the presence of educational technology in the digitalization era. Likewise social media learning can support and be useful in improving the quality of teaching staff and their job satisfaction and advanced learning for Christian religious education